The Influence of Maternal Acceptance-Rejection and Adolescents Self Esteem to Bullying Behavior Junior High School Students - Siti Aviani Nur Azizah; Dwi Hastuti (Journal of Family Sciences, 2019)
This study aimed to analyze the influence of maternal acceptance-rejection and self-esteem adolescents on bullying behavior of junior high school students. The study took place at two junior high schools located in Bogor City and involved 86 students who were selected using simple random sampling. The measuring instrument used in this study was a PAR adaptation from Rohner (1986) with a reliability of 0.785, self-esteem instrument adaptation from Rosenberg's (1965) with a reliability of 0.773, and a bullying behavior instrument adaptation from Hastuti, Herien, and Djaswelma (2015) with the reliability of 0.902. Data analysis used in this study was descriptive statistical analyses and statistical analyses of Pearson correlation and linear regression tests. The data were collected using self-administered questionnaires guided by the researcher. The results showed that more than half of adolescents had perceptions of affective parenting. However, about 40 percent of adolescents have self-esteem in the low category. The most common type of bullying behavior adolescents is verbal bullying. The test results showed that parents with aggression and undifferentiated rejection are unfortunately related to the adolescents’ bullying, and low adolescents’ self-esteem is followed by bullying behavior. Gender (male adolescents) and low self-esteem had a significant effect on bullying behavior. Meanwhile, parental rejection had a significant positive effect on bullying behavior.